A sequential explanatory mixed methods investigation of e-government outcomes evaluation practice in developing countries: South Africa as context - Boamah-Abu, Charles (Department of Information Systems, 2022)
E-government has become de rigueur in public service delivery. Attendant to the growing adoption is the need to establish the extent to which investments are yielding desired outcomes and how the services can be improved. E-government evaluation is, therefore, an important research problem— more so in developing countries, where resources are scarce, and the opportunity cost is higher. This, notwithstanding, there is a paucity of research. This research explored the “lay of the land”, to describe e-government outcomes evaluation practice in developing countries. South Africa was selected as context; the sample consisted of public sector employees. Practice theory was adopted to frame e-government evaluation as what people do. A two-phased sequential explanatory mixed methods strategy, supported by post-positivism, was employed. This allowed examination of the different aspects of practice— the tangible (e.g., activities) and the intangibles (e.g., affective issues). In the quantitative phase, questionnaire data from 106 public employees (i.e., managers and non-managers from IT, Evaluation, and Other backgrounds) was analysed with factor and cluster analyses techniques to identify the important elements which described e-government outcomes evaluation practice and the patterns of performance. This was followed by a qualitative phase in which interview transcripts of 12 participants drawn from the sample of the preceding phase, four from each background (i.e., two from management and nonmanagement respectively), were analysed with content analysis to help understand the results of the quantitative phase. The findings show an inadequate organizational capacity to evaluate e-government outcomes and use the results. The primary purpose of evaluation is compliance, and organizational outcomes are mostly measured. While there may be some degree of use (e.g., learning, i.e., conceptual) recommendations may not be implemented. Furthermore, there were significant differences among participants; evaluation and IT managers with the requisite expertise were likely to have a positive perception of e-government outcomes evaluation practice. This research adds value to e-government outcomes evaluation research and practice in developing countries, and also to the methodological development of practice theory in Information Systems (IS). Consistent with research on practice, recommendations are drawn to help e-government evaluation stakeholders improve future practice and, thereby, ameliorate the high e-government failure rate. The findings shed light on current practice, e.g., what is done well and challenges, and add to the otherwise sparse body of knowledge in the domain under investigation. A deterrent to the adoption of practice theory is the paucity of theoretical and conceptual frameworks. This research illustrates how Schatzki's theory can be applied to investigate an IS problem and helps remedy the dearth of empirical research on practice. Furthermore, it contributes to the current effort to develop mixed methods in IS— and practice research in general. The agenda for future research can help advance the, hitherto, under researched domain of e-government evaluation in developing countries.